The African perception of death, with special reference to the Zulu : a critical analysis - Jali, Nozizwe Martha (Stellenbosch : University of Stellenbosch, 2010)
99 leaves printed on single pages, preliminary pages and numberd pages 1-87. Includes bibliography. Digitized at 600 dpi grayscale to pdf format (OCR), using a Bizhub 250 Konica Minolta Scanner.